Somerset Hall, St. Dorothy. ([Place of publication not identified] : [publisher not identified], 1811)
The diagram represents Somerset Hall Plantation and several other plantations in the parish of St. Catherine. Somerset Hall plantation was divided into lots and sold to various individuals. It is bounded on the left by a run of land called Old House, containing 55 acres and belongs to Master's estate. The diagram also shows other estates such as Spring estate containing 314 acres and sold to Mr W M Kingsburg in 1783. There are also two other promiment estates represented on the diagram Woodhall Estate and Mount Pleasant Plantation.
St Catherine.
Keywords: Saint Catherine (Jamaica) -- Maps; Jamaica -- Maps; Jamaica; Jamaica -- Saint Catherine; Maps